2020
DOI: 10.1073/pnas.2015083117
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin topology and the timing of enhancer function at the HoxD locus

Abstract: The HoxD gene cluster is critical for proper limb formation in tetrapods. In the emerging limb buds, different subgroups of Hoxd genes respond first to a proximal regulatory signal, then to a distal signal that organizes digits. These two regulations are exclusive from one another and emanate from two distinct topologically associating domains (TADs) flanking HoxD, both containing a range of appropriate enhancer sequences. The telomeric TAD (T-DOM) contains several enhancers active in presumptive forearm cells… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 64 publications
(113 reference statements)
4
33
0
Order By: Relevance
“…S3, blue arrowhead). Also, as previously reported (Rodriguez-Carballo et al, 2017;Rodríguez-Carballo et al, 2020;Yakushiji-Kaminatsui et al, 2018), a cluster of CTCF binding sites delimits the boundary between the mouse and the chicken sub-TAD1 and sub-TAD2, thus making the transition between the D4 and D9 regions in both species (Fig. 2; Fig.…”
Section: Conserved Paralogous Regulatory Landscapessupporting
confidence: 73%
“…S3, blue arrowhead). Also, as previously reported (Rodriguez-Carballo et al, 2017;Rodríguez-Carballo et al, 2020;Yakushiji-Kaminatsui et al, 2018), a cluster of CTCF binding sites delimits the boundary between the mouse and the chicken sub-TAD1 and sub-TAD2, thus making the transition between the D4 and D9 regions in both species (Fig. 2; Fig.…”
Section: Conserved Paralogous Regulatory Landscapessupporting
confidence: 73%
“…Such losses could be explained when looking at variations in chromatin topology. For example, mutations in all five CTCF sites considerably weakened contacts between the cluster and T-DOMb, where most proximal enhancers are located (Andrey et al, 2013;Rodríguez-Carballo et al, 2020). These contacts were redirected towards T-DOMa, which is poor in proximal enhancers, but rich in other regulations, leading to the ectopic expressions described above, concomitantly to a loss of expression in proximal limbs.…”
Section: The Impact Of Cbs For Hoxd Gene Regulation In Limb Budsmentioning
confidence: 97%
“…During limb development, various subsets of Hoxd genes respond first to T-DOM-located proximal enhancers, then to C-DOM-located digit enhancers (Andrey et al, 2013). Because the two subgroups of target genes are delimited by CTCF sites, it was suggested that such CBSs may specify, through a 3D structure, particular enhancer-promoter interactions leading to these bimodal transcription patterns (Rodríguez-Carballo et al, 2020). However, the most visible effect observed across the different mutant lines generated in this study was more quantitative than qualitative and no obvious mis-expression of target gene subgroups was scored.…”
Section: The Impact Of Cbs For Hoxd Gene Regulation In Limb Budsmentioning
confidence: 99%
“…For instance, the duplication of the HOXD cluster reported in ref. 1 includes the ELCR2 proximal limb enhancer 63 . In the mutant chromosome, a copy of HOXD13 is in close proximity with this enhancer, regardless of the orientation of the duplicated DNA sequence and will thus receive proximal regulatory inputs (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%